Assessing the Performance of Urban Drainage Networks in Settlements as an Impact of Urbanization - Jeni Paressa,; Dina Limbong Pamuttu,; Siti Nur Indah Sari,; Dina Limbong Pamuttu,; Aring Wulandari, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The increase in the number of residents in the city area due to urbanization and the rapid growth of the city's population itself causes many environmental problems, one of which is flooding. The drainage network becomes a vital infrastructure in the development of the city to be free from flood problems, especially in dense areas such as settlements or housing, which are increasingly densely populated every year. The purpose of this study is to examine whether the drainage network in the Berlian Simpati Blorep housing estate in the middle of Merauke City is able to accommodate flood discharge for the next few years. The methods used in this study are quantitative and qualitative, based on the results of the analysis. The results showed that with an existing channel capacity (Qs) of 0.097 m3/sec < the planned flood calculation discharge (Qr) of 13.657 m3/sec, the existing channel capacity was not able to function effectively with a 5-year recurrence period.